2022
DOI: 10.2306/scienceasia1513-1874.2022.048
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and biological activities of the gamma-irradiated blended fibroin/aloe gel film

Abstract: The physicochemical and biological properties of the blended fibroin/aloe gel film as a wound dressing were investigated to support the wound healing efficacy of the film described in our previous study. In the current study, protein content, molecular weight pattern, and chemical characteristics of the silk fibroin and the aloe gel extracts were analyzed. The two extracts were then dissolved in lactic acid solution and casted to obtain the blended fibroin/aloe gel film. We found that gamma irradiation did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…These results implied that the film extract behaved as having a noncytotoxicity effect on fibroblast cells and might also have the potential to stimulate cell viability and proliferation. Also, the results were similar to our previous study …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results implied that the film extract behaved as having a noncytotoxicity effect on fibroblast cells and might also have the potential to stimulate cell viability and proliferation. Also, the results were similar to our previous study …”
Section: Discussionsupporting
confidence: 92%
“…As the depicted cell cycle data implies, the film-treated cells shifted from the G0/G1 phase to the S phase by binding to cyclin D/CDK4,6 complexes that regulate G1-S phase transit. The film extract promoted cells to enter the S phase via the pathway of acemannan, which is an important stage for mitosis and cell growth by influencing cyclin-dependent cell cycle progress through translational regulation of cyclin D1 . Our cell cycle finding was liable to Yuan et al who reported that after treating with aloe polysaccharide, the number of cells was increased in the S and G2/M phases preparing for mitosis, and cyclin D1 protein was upregulated in a concentration-dependent manner .…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations